FeOOH Nanocubes Anchored on Carbon Ribbons for Use in Li/O2 Batteries. Issue 12 (4th February 2019) - Lin, Zhipeng; Zhang, Hao; Liang, Guofeng; Jin, Yanqi; Zeng, Hongbin; Li, Jiawang; Chen, Jian; Zhang, Weihong; Xie, Fangyan; Jin, Yanshuo; Meng, Hui
Abstract: A composite of FeOOH nanocubes anchored on carbon ribbons has been synthesized and used as a cathode material for Li/O2 batteries. Fe 2+ ion‐exchanged resin serves as a precursor for both FeOOH nanocubes and carbon ribbons, which are formed simultaneously. The as‐prepared FeOOH cubes are proposed to have a core–shell structure, with FeOOH as the shell and Prussian blue as the core, based on information from XPS, TEM, and EDS mapping. As a cathode material for Li/O2 batteries, FeOOH delivers a specific capacity of 14816 mA h g −1 cathode with a cycling stability of 67 cycles over 400 h. The high performance is related to the low overpotential of the oxygen reduction/evolution reaction on FeOOH. The cube structure, the supporting carbon ribbons, and the ‐OOH moieties all contribute to the low overpotential. The discharge product Li2 O2 can be efficiently decomposed in the FeOOH cathode after a charging process, leading to higher cycling stability. Its high activity and stability make FeOOH a good candidate for use in non‐aqueous Li/O2 batteries. Abstract : Composite nanostructured cathode : FeOOH nanocubes with a core–shell structure and anchored on carbon ribbons have been prepared. The carbon ribbons improve the conductivity of the system and make more of the FeOOH surface available for electrochemical reaction. An Li/O2 battery with FeOOH as the cathode material shows a specific capacity of 14816 mAh g −1 cathode and a long‐term stability of 67 cycles over 400 h (see figure).